Bosnian War Horrors: Dr. Haris Silajdzic
Short report on CBS evening news discusses steps US and UN have taken to enforce no-fly zone, safety of UN troops. Dr Harris Silajdzic talks about extermination of a people, deaths of 20.000. children.